Analysis of the Effect of Clarity, Efficiency, Accuracy, Stimulation, and Novelty on the Attraction of Using PayLater Services - Mutiara Cahyani; Siti Jamilah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of five independent variables—perspicuity, efficiency, dependability, stimulation, and novelty—on the attractiveness of PayLater services, and their impact on user decisions in using the service. The research method used is quantitative with an associative approach and multiple linear regression analysis techniques through SEM-PLS. The results of the validity test show that all indicators have an outer loading value > 0.7, while the composite reliability and AVE values ​​indicate the consistency and validity of the construct. The goodness-of-fit model test produces an SRMR value of 0.051 (<0.08), indicating that the model is appropriate. The R-square value of 0.777 indicates that 77.7% of the variation in attractiveness is explained by the five independent variables. The F-square test shows that stimulation has a moderate effect (0.157), while other variables have a small effect (values ​​between 0.067–0.114). Path analysis shows that all hypotheses are significantly accepted (p < 0.05), with stimulation having the strongest influence on attractiveness. This finding reinforces the importance of innovation, emotional, and system clarity elements in driving user interest in PayLater services in the e-commerce ecosystem.